DDX3X and virus interactions: functional diversity and antiviral strategies - Ma, Shengming; Mao, Qian; Weng, Shaoting; Teng, Man; Luo, Jun; Zhang, Kunpeng (Frontiers in Microbiology, 2025)
As a core member of the DEAD-box helicase family, DDX3X modulates RNA metabolic networks through its ATPase activity, RNA helicase function, and nucleic acid-binding capacity to participate in bidirectional regulation of innate immune responses and virus-host interactions. Multiple viruses achieve effective genome replication and immune evasion by hijacking DDX3X’s enzymatic activities or interfering with its mediated immune signaling transduction. Nevertheless, hosts have evolved strategies to exploit DDX3X for activating interferon signaling pathways and other antiviral mechanisms, establishing multilayered defense networks. This review systematically elaborates the functional diversity exhibited by DDX3X protein in virus interaction networks. DDX3X orchestrates viral genomic RNA processing during replication. Simultaneously, it interacts with host restriction factors to evade antiviral immunity, establishing a dynamic balance between viral propagation and host defense. The functional plasticity of DDX3X not only elucidates immune regulatory mechanisms in host-pathogen coevolution, but also provides novel molecular perspectives for deciphering zoonotic transmission barriers.